The Olympic Games of Beijing: Mobility, Environment and New Technologies - Fistola, Romano (TeMA - Journal of Land Use, Mobility and Environment, 2008)
The environmental condition of Beijing is characterized by high level of entropy mainly referable to the air pollution that considerably affects the conditions of urban life. The basic idea of this text is to succeed in finding a thread among some building realizations and infrastructures in course of completion and in verifying, also thanks to the use of advanced technologies, the entropic or neghentropic contribution to the actual quality of life in the Chinese capital. The buildings considered useful for an investigation are the following: The Olympic Stadium, destined to entertain about 90 thousand spectators and covered with more than one thousand solar panels to satisfy the whole energetic requirement of the structure and of the surrounding area; the National Aquatic Centre (known as “water cube”) inside which competitions of aquatic sports will take place and thanks to the new technologies it will be possible to recycle tons of water a year; the new terminal n.3 of the Beijing Capital Airport, designed by Sir Norman Foster, which will become, with its 66 million passengers, the biggest terminal all over the world. The paper describes the sudden transformations that the Chinese capital is undergoing in the last years, which are contributing to conform its new pattern of world city reshaped to the western model.